Luiz Antônio dos Santos Lima e o seu legado educacional (Natal/RN, 1910-1961) - Costa, Karoline Louise Silva da (2013)
This research aims to analyze the intellectual practice of Luiz Antônio Ferreira Souto dos Santos Lima. This is done considering the author´s legacy related to the History of Education in Rio Grande do Norte/Brazil in the time span of 1910 to 1961. Thus, the research is grounded on assumptions that rely on the Cultural History field. The research also dealt with dialogues between the author and Chartier (1990), Elias (1994), Morais (2003; 2006), as well as Gondra (2003). For the bibliographical research the work dealt with a vast array of documents such as newspapers called A República and Diário do Natal, Pedagogium, Revista do ensino, as well as state laws and decrees These documents were obtained at the Historical and Geographical Institute in Rio Grande do Norte. The research also dealt with School Bylaws and a medical doctoral thesis called Mental Hygiene and Education that was written by Luiz Antônio dos Santos Lima. Other documents were obtained at the State´s Public Archive, such as the Book of Honor, Work Records, Reports and Minutes of the General Directorate of Public Instruction Meetings. It was possible to infer that professor Luiz Antônio dos Santos Lima was teacher at Grupo Escolar Augusto Severo, the Atheneu as well as some local grade schools. The professor had a broad role in society, in administrative positions such as the Presidency of the Association of Teachers of Rio Grande do Norte, as Grade School Director in the School of Pharmacy and the State Education Department. He was also a member of the Academy of Arts and a partner at Historical and Geographical Institute in Rio Grande do Norte. The professor has also concerned with issues related to teaching good habits such as feeding, grooming, discipline, game morals, temperance, smoking, sex education; all of which necessary for the formation of healthy children. He was an enthusiast of an intuitive method and teaching lessons through practice, that he considered key elements in education. It is seen that professor Luiz Antônio dos Santos Lima had presence in the State´s health education and that his ideals were line with the ideal of modernity of the early twentieth century